Depressive disorders with a predominance of apathic-adynamic or anxiety-phobic syndroms: correlation of clinical signs and search activity - Лисюк, Алевтина; Pyliagina, Galyna (Psychosomatic Medicine and General Practice, 2022)
SUMMARY Topicality. In today’s world, depressive disorders (DD) are one of the most common mental disorders. DD causes disturbances in various areas of human mental activity, significantly affecting the quality of life, as well as impairing the ability to understand and properly assess the future. The need to develop new strategies for diagnosis and therapy. In addition to the main groups of symptoms in DD should pay attention to clinical and psychopathological syndromes: depressive, asthenic, apathetic, anxiety-phobic, somato-vegetative and hypochondriac. at DD and will need further research. The aim of the study. Explore the severity of apathic-adynamic or anxiety-phobic symptoms in DD, their nosological affiliation in relation to the level of MLO. Methods. We examined 66 patients of both sexes (36 women and 30 men) aged 18 to 40 years (24.4 ± 3.8) with different types of DD, diagnosed according to the criteria of the International Classification of 10 revisions. A clinical-psychopathological method (semi-structured clinical-diagnostic interview) was used to determine apatic-adynamic (AA) or anxiety-phobic (AF) variants of DD. According to the clinical picture, patients are divided into 2 groups: the first - patients with apatic-adynamic symptoms, the second - with anxiety-phobic symptoms. The PHQ-9 patient health questionnaire was used to assess the severity of depression. We used the Test of meaningful life orientation, Leontiev), adapted by D. Leontiev version of the test J. Crambo, L. Maholic "Purpose-in-Life Test". The article examines and analyzes the difference between depressive disorders (DD) and the leading anxiety-phobic and apathic-dynamic symptoms. Results. Significantly lower indicators were found in the scales of goal presence, interest in life, life satisfaction (effectiveness, self-realization) and the ability to control one’s life in general in the presence of apatic-dynamic symptoms of DD compared to anxiety-phobic symptoms. The presence of a statistically significant difference indicates possible therapeutic targets in patients of these two groups.